Digital Investment Toolkit: Improving the Conceptual Framework - A. I. Goncharov; M. V. Goncharova; A. A. Orlova (Финансы: теория и практика)
The article develops the issues of application in investment practice of a number of official terms related to the turnover of digital financial assets as a subject of research. Their economic and legal content in the focus of the research objective is achieved by solving scientific tasks - determining the functional purpose of monetary claims as one of the types of digital financial assets and critically evaluating the relevant conceptual apparatus available in the current regulatory framework. Combination of general scientific, private scientific and special methods of cognition is used on the methodological basis of materialistic positivism. The doctrinal sources were the relevant scientific works of domestic and foreign authors, the materials of the official statistics of the Bank of Russia, credit institutions, professional participants in the financial market, specialized companies-operators as of 01 2025 were used as a statistical base. As a result, an empirical study of investment transactions made it possible to reveal the investment and economic content of digital financial assets in terms of their first variety - monetary claims. The conclusions were substantiated that the current regulatory provisions of Federal Law No. 259-FZ dated 31.07.2020 require adjustments in terms of clarification of both individual definitions and interpretations of a number of provisions concerning the conceptual apparatus. Based on the identification of the economic and legal nature and interpretation of type elements of the investment toolkit of digital financial assets, the authors propose relevant recommendations.